2010
DOI: 10.1002/cjoc.201090265
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Propane to Propylene over Ga2O3Supported on Mesoporous HZSM‐5 in the Presence of CO2

Abstract: Dehydrogenation of propane to propylene over mesoporous HZSM-5 supported Ga 2 O 3 catalysts in the presence of CO 2 has been investigated, and compared with that of conventional HZSM-5 supported one. The initial activity of the catalysts descends while the stability and selectivity to propylene improve with increasing the Si/Al ratios of the support. The optimal Si/Al ratio is 240 for the propylene yield reaching 21.7% after reaction for 50 h. The introduction of the mesopores improves the activity as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…29 Hierarchical H-ZSM-5 has also been used as a support for impregnation of Ga 2 O 3 for oxidative dehydrogenation reactions. 30 The above reports are encouraging for the application of hierarchical zeolites to PDH and related reactions. In this work, we focus on direct incorporation of gallium (Ga) sites during the formation of silica MFI hierarchical zeolites.…”
Section: ■ Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…29 Hierarchical H-ZSM-5 has also been used as a support for impregnation of Ga 2 O 3 for oxidative dehydrogenation reactions. 30 The above reports are encouraging for the application of hierarchical zeolites to PDH and related reactions. In this work, we focus on direct incorporation of gallium (Ga) sites during the formation of silica MFI hierarchical zeolites.…”
Section: ■ Introductionmentioning
confidence: 78%
“…For example, hierarchical MFI (in the aluminosilicate form, ZSM-5) has been used as a support to impregnate PtSnNa catalysts with improved PDH conversion and selectivity and lower deactivation compared to bulk ZSM-5 supports . Hierarchical H-ZSM-5 has also been used as a support for impregnation of Ga 2 O 3 for oxidative dehydrogenation reactions . The above reports are encouraging for the application of hierarchical zeolites to PDH and related reactions.…”
Section: Introductionmentioning
confidence: 94%
“…On the one hand, for the intracrystalline mesopores, the average pore size is far less than the particle size of platinum and the Pt particles cannot enter these pores in the catalyst. However, according to the results of Yue' group, due to the better transport of the reactant and product molecules, the introduction of these intracrystalline mesopores in ZSM‐5 improves the catalytic activity as well as the stability of the catalyst. On the other hand, for the large pores on the surface of the catalyst, these pores are large enough to anchor the platinum particles inside.…”
Section: Resultsmentioning
confidence: 99%
“…However, the negative effects of CO 2 addition and rapid deactivation have prevented Ga 2 O 3 catalysts from receiving more attention in the same group. Following this hint, various studies by Gao et al [68–73] . showed that β‐Ga 2 O 3 with unsaturated Ga 3+ cations and abundant strong acid sites on the surface was the main active species.…”
Section: Development Of Metal Oxides In Co2−odpmentioning
confidence: 93%